2022
DOI: 10.3389/fnut.2022.957391
|View full text |Cite
|
Sign up to set email alerts
|

Collagen peptide promotes DSS-induced colitis by disturbing gut microbiota and regulation of macrophage polarization

Abstract: Ulcerative colitis (UC) is an inflammatory bowel disease caused by mucosal immune system disorder, which has increased steadily all over the world. Previous studies have shown that collagen peptide (CP) has various beneficial biological activities, it is not clear whether the effect of CP on UC is positive or negative. In this study, 2.5% dextran sulfate sodium (DSS) was used to establish acute colitis in mice. Our results suggested that CP supplementation (200, 400 mg/kg/day) promoted the progression of colit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The level of MDA and the activity of SOD in serum were also improved by C-PC [ 27 ]. The gut microbiota may also be involved in these inflammation diseases [ 42 ]. Altogether, it’s a complex process to delay senility in vivo for C-PC which needs further research in future.…”
Section: Discussionmentioning
confidence: 99%
“…The level of MDA and the activity of SOD in serum were also improved by C-PC [ 27 ]. The gut microbiota may also be involved in these inflammation diseases [ 42 ]. Altogether, it’s a complex process to delay senility in vivo for C-PC which needs further research in future.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to the transmembrane pattern recognition receptors of bacteria being revitalized, which disrupts the balance of immunity, eventually activating the inflammatory pathways of NF‐κB, Akt, and MAPK, and stimulating the discharge of inflammatory cytokines, promoting immune response, and damage to the intestinal mucosal barrier 52‐55 . IL‐6 plays a significant regulatory role in the pathogenesis of UC, which can activate the STAT3 and NF‐κB signaling pathway that further increase the permeability of epithelial cells and enhance intestinal mucosal injury 56,57 . NF‐κB is considered to play a key role in the release of proinflammatory mediators; it has been reported that colonic inflammation can be alleviated by inhibiting the translocation of p65 from the cytosol to the nucleus, the phosphorylation and degradation of IκB‐α, and suppression of the expressions of NF‐κB‐related proteins 58 .…”
Section: Discussionmentioning
confidence: 99%
“…[52][53][54][55] IL-6 plays a significant regulatory role in the pathogenesis of UC, which can activate the STAT3 and NF-κB signaling pathway that further increase the permeability of epithelial cells and enhance intestinal mucosal injury. 56,57 NF-κB is considered to play a key role in the release of proinflammatory mediators; it has been reported that colonic inflammation can be alleviated by inhibiting the translocation of p65 from the cytosol to the nucleus, the phosphorylation and degradation of IκB-⊍, and suppression of the expressions of NF-κB-related proteins. 58 IL-6 was significantly increased in mice with DSS-induced colitis, which might be involved in the regulation of signaling pathways such as apoptosis, migration, and protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Green tea extract containing piper retrofractum fruit inhibits DSS-induced colonic inflammation by reducing the expression of miR-21 and NF-κB [ 25 ]. Collagen peptide promotes DSS-induced colitis by disrupting the gut microbiota and controlling macrophage polarization [ 26 ]. The Maillard product of ovalbumin blocks the release of lysine and essential amino acids, as well as improves the gut microbiota and levels of short-chain fatty acids in vivo [ 11 ].…”
Section: Discussionmentioning
confidence: 99%